Impact of Immune Cells in the Tumor Microenvironment of Prostate Cancer Metastasis - Justin K. Messex; Geou-Yarh Liou (Life, 2023)
Prostate cancer is the most prevalent type of cancer in senior American men. Currently, the five-year survival rate after the initial diagnosis of prostate cancer is close to 100%. However, it is also the second leading cause of cancer death in senior men due to the dissemination of prostate cancer cells outside of the prostate causing growth in other organs, known as metastatic prostate cancer. The tumor microenvironment (TME) plays a critical role in the development, progression and metastasis of prostate cancer. One of the major components of the TME contains various types of immune cells, often recruited by cancer cells to the cancer formation areas. The interactions among prostate cancer cells and the infiltrating immune cells affect the outcome of prostate cancer. Here, we summarize the mechanisms various infiltrating immune cells use to regulate prostate cancer metastasis and possibly lead to the development of treatment strategies. Furthermore, the information here may also give rise to preventative strategies that focus on targeting the TME of prostate cancer patients.